2021
DOI: 10.3390/ma15010168
|View full text |Cite
|
Sign up to set email alerts
|

Gallium-Indium-Tin Eutectic as a Self-Healing Room-Temperature Liquid Metal Anode for High-Capacity Lithium-Ion Batteries

Abstract: Owing to their intrinsic properties, such as deformability, high electrical conductivity, and superior electrochemical performance, room-temperature liquid metals and liquid metal alloys have attracted the attention of researchers for a wide variety of applications, including portable and large-scale energy storage applications. In this study, novel gallium-indium-tin eutectic (EGaInSn) room-temperature liquid metal nanoparticles synthesized using a facile and scalable probe-ultrasonication method were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…To characterise the electrochemical performance of the eGaSn@TiO 2 NDs negative electrode, a CV test was performed in a voltage range of 0–2 V (vs. Li + /Li) at a scan rate of 0.05 mV s −1 (Figure 3a). In the scans of three cycles, four repeatable reduction peaks are observed at approximately 0.41, 0.54, 0.57, and 0.71 V, corresponding to the alloying reaction of Ga with Li + [13,21] . The cathodic peak at 0.48 V corresponds to the alloying of Li with Sn [27–29] .…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…To characterise the electrochemical performance of the eGaSn@TiO 2 NDs negative electrode, a CV test was performed in a voltage range of 0–2 V (vs. Li + /Li) at a scan rate of 0.05 mV s −1 (Figure 3a). In the scans of three cycles, four repeatable reduction peaks are observed at approximately 0.41, 0.54, 0.57, and 0.71 V, corresponding to the alloying reaction of Ga with Li + [13,21] . The cathodic peak at 0.48 V corresponds to the alloying of Li with Sn [27–29] .…”
Section: Resultsmentioning
confidence: 95%
“…In the scans of three cycles, four repeatable reduction peaks are observed at approximately 0.41, 0.54, 0.57, and 0.71 V, corresponding to the alloying reaction of Ga with Li + . [13,21] The cathodic peak at 0.48 V corresponds to the alloying of Li with Sn. [27][28][29] The cathodic peak at 0.75 V is associated with the reduction of the oxygen-containing functional groups of Ga 3 + .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From SEM imaging and EDX analysis (Figure 3) it was found that the morphology of the GaInSn film changes after 1 hour of nitrate reduction. For Galinstan an even distribution of Ga, In and Sn elements should occur [17] and the In : Sn ratio should be 2 : 1, however after nitrate reduction, not only does the morphology change, but the In : Sn ratio increases in many areas of the electrode indicating the formation of In−Sn rich regions within the predominantly Ga film. This is seen in the EDX mapping images showing the accumulation and co‐location of In and Sn elements (Figure 3) while an EDX spectrum of one of these areas is shown in Figure S5 indicating a higher composition of In.…”
Section: Figurementioning
confidence: 99%